La Educación Familiar En Salud Y Sus Consecuencias En Los Hábitos De Higiene De Los Niños Y Niñas Del Primer Año De Educación Básica En La Unidad Educativa “Guillermo Baquerizo Jiménez” Del Cantón Babahoyo. - Vega Jiménez, Gladys Viviana (2015)
Determine hygiene habits that can be linked into the education system, it is no easy task, for its management arises implement a system that allows to improve or increase effective hygiene habits. In the micro curriculum planning skills are not considered to develop healthy habits. It is proposed to link into the school curriculum the practice of hygiene, through hygiene guide. The benefit provided by the application of the Guide to Hygiene within the Education Unit "Guillermo Baquerizo Jimenez" Canton Babahoyo "is of socio-cultural, since it allows the child and the child cope with integrity, without fear of self-conscious and They are rejected by their peers within the school environment. Its importance lies in the ability to respond favorably to enthusiastically performance objectives care cleanliness and hygiene in infants. This requires people to act in a proper way, with the right combination of knowledge and skills to address this problem and help children to improve their personal appearance at school and at home.